Minutes of the 43rd Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 42nd Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 42nd Meeting of the Academic Council. 3. Changes in Post-Graduate Program in Disaster Management (PPDM). 4. Miscellaneous: 4.1.1. Request for Regularization of Credits Earned by a Student. 4.2.1. 7th Convocation. 4.3.1. Introducing programs on Gender Study and Anthropology. 4.4.1. Review of the syllabus.